Reaction rates of lignin and hexenuronic acids with chlorine dioxide, ozone, and a sulfuric acid - Ventorim, Gustavo; Colodette, Jorge Luiz; Gomes, Adriana de Fatima; da Silva, Luiz Henrique Mendes (My University, 2008)
The reaction rates of lignin and hexenuronic acids (HexA) with chlorine dioxide, ozone, and sulfuric acid were investigated. In unbleached and oxygen-delignified eucalyptus kraft pulps containing both lignin and HexA, only HexA, or only lignin reacted with chlorine dioxide, ozone, and sulfuric acid under typical bleaching conditions. The maximum reaction rates of chlorine dioxide with lignin and HexA were 57.2 and 26 mmol/kg/min, respectively, for unbleached pulp, and 26.7 and 13 mmol/kg/ min, respectively, for oxygen-delignified pulp. The maximum reaction rates of ozone with lignin and HexA were 58.6 and 132 mmol/kg/min, respectively, for unbleached pulp, and 56.8 and 134 mmol/kg/min, respectively, for oxygen-delignified pulp. The maximum reaction rates of sulfuric acid with lignin, and HexA were 1.11 and 0.93 mmol/kg/min, respectively, for unbleached pulp, and 1.95 and 0.80 mmol/kg/min, respectively, for oxygen-delignified pulp. Chlorine dioxide reacts faster with HexA in the presence of the residual lignin. The kinetic results suggest that pulp treatment with ozone, when justifiable, should follow but not precede chlorine dioxide oxidation. Unbleached pulp residual lignin and HexA react twice as fast with chlorine dioxide than the lignin and HexA present in oxygen-delignified pulp, while the pulp type has no significant effect on lignin and HexA reactivity toward ozone. HexA reactions with sulfuric acid and ozone can be described by two-phase pseudo first-order reaction rates. © 2008 by the Society of Wood Science and Technology.
Keywords: Chlorine dioxide; Eucalyptus; Hexenuronic acids; Kraft pulp; Lignin; Ozone; Reaction rates; Sulfuric acid